Implementation Of Benson Relaxation Therapy for Pain Reduction in Post-Caeserean Patient Section in the An-Nisa Ward at Bakti Timah Hospital Pangkal Pinang - Veronica Agustina Sihotang; Witri Hastuti (Jurnal EduHealth, 2026)
Sectio caesarea is a surgical delivery procedure that may cause acute pain in the abdominal incision area. If not managed properly, pain may inhibit mobilization, disturb rest, reduce comfort, and slow the recovery process of post sectio caesarea mothers. One non-pharmacological intervention that can be used to help reduce pain is Benson relaxation therapy. This case study aimed to describe the implementation of maternity nursing care using Benson relaxation therapy to reduce pain in post sectio caesarea patients in the An-Nisa Ward of Bakti Timah Hospital, Pangkalpinang. This study used a descriptive case study method involving two patients, Mrs. B and Mrs. R, who met the criteria of being post sectio caesarea patients aged 21-40 years, fully conscious, able to communicate verbally, cooperative, and willing to participate. Data were collected through interviews, observation, physical examination, documentation review, and pain intensity measurement using the Numeric Rating Scale (NRS). Benson relaxation therapy was provided for three days, twice daily, for approximately 10 minutes each session. The results showed a gradual decrease in pain intensity. In Mrs. B, the initial pain score of 6 decreased to 3 on the third day after the intervention. In Mrs. R, the initial pain score of 5 decreased to 3 on the third day after the intervention. Both patients appeared more relaxed, more comfortable, and were able to begin light mobilization. This case study concludes that Benson relaxation therapy can help reduce pain intensity in post sectio caesarea patients and can be applied as a safe, simple, and easy non-pharmacological nursing intervention.